Non-toxigenic Bacteroides fragilis (NTBF) administration reduces bacteria-driven chronic colitis and tumor development independent of polysaccharide A - Chan, June L.; Wu, Shaoguang; Geis, Abby L.; Chan, Gabrielle V.; Gomes, Talles A.M.; Beck, Sarah E.; Wu, Xinqun; Fan, Hongni; Tam, Ada J.; Chung, Liam; Ding, Hua; Wang, Hao; et al. (Mucosal immunology, 2019)
Polysaccharide A (PSA), an immunogenic capsular component of non-toxigenic Bacteroides fragilis (NTBF) strain NCTC 9343, is reported to promote mucosal immune development and suppress colitis. Contrastingly, enterotoxigenic Bacteroides fragilis (ETBF) is highly associated with inflammatory bowel disease (IBD) and colorectal cancer (CRC), rapidly inducing IL-17-dependent murine colitis and tumorigenesis. In specific-pathogen-free (SPF) C57BL/6 wild-type (WT) and multiple intestinal neoplasia (MinApc716+/−) mice, we show that sequential treatment of the NTBF strain, 9343, followed by the ETBF strain, 86-5443-2-2 (86), diminished colitis and tumorigenesis. Mice treated simultaneously with 9343 and 86 exhibited both severe colitis and tumorigenesis. Abrogated disease severity in sequentially treated mice was attributed to 9343 strain dominance and decreased IL-17A, but 86 colonization prior to or simultaneous with 9343 mitigated the anti-inflammatory effect of 9343. Remarkably, 9343-mediated protection was independent of PSA, as sequentially treated mice receiving ΔPSA 9343 exhibited similar protection. Further, SPF WT and Min mice colonized with PSA-competent or PSA-deficient 9343 exhibited similar IL-10, IL-17, and IFN-γ responses. Treatment of 86-colonized mice with 9343 failed to disrupt 86 pathogenesis. Our findings demonstrate that 9343 colonization, independent of PSA, offers prophylaxis against colitis-inducing 86 but may not be a valid therapy once colitis is established.